Comparative Analysis of Implicit Sentiment Detection with Causal and Prompt-Based LLMs - Jesus, Marco Antônio Martins Ribeiro de; Esmin, Ahmed (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2025)
Implicit Sentiment Analysis (ISA) remains a challenging NLP problem, as models frequently rely on superficial shortcuts rather than deep contextual cues. This paper directly contrasts two paradigms: a specialized causal model named CLEAN, designed for robustness against spurious correlations and built on a BERT backbone, and a suite of modern open-source large language models (LLMs) such as Llama-3, Gemma-3, Qwen-3, and DeepSeek-R1, executed locally via a streamlined deployment framework. Experiments using widely recognized benchmarks for sentiment analysis reveal that, although prompted LLMs markedly outperform traditional fine-tuning, the causal CLEAN model retains a robustness advantage on the most subtle implicit cases. Our analysis clarifies current trade-offs between the broad versatility of LLMs and the targeted precision of causal methods. As future work, we highlight three directions: (i) combining causal regularization techniques with parameter-efficient fine-tuning approaches like low-rank adaptation methods to fuse both strengths, (ii) extending evaluation to cross-domain and multilingual ISA scenarios, and (iii) integrating explanation-based feedback loops to further reduce shortcut learning observed in prior approaches to sentiment analysis.